Embracing Freedom in Learning: The Impact of Kurikulum Merdeka on Engineering Students of Universitas Negeri Medan - Hasan, Hanapi; Maksum, Hasan; Waskito; Tansa Trisna Astono Putri (The Indonesian Journal of Computer Science, 2024)
In 2020, Indonesia's Ministry of Education, Culture, Research, and Technology introduced the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum for higher education to better prepare students for the modern job market. This study contrasts the MBKM curriculum with the non-MBKM curriculum, focusing on their impacts on students' career exploration and professional maturity. Using a quantitative, correlational approach, the study sampled 187 engineering students from a Medan university. Instruments included the Career Exploration Survey (CES) and the Career Development Inventory (CDI). Results showed that both curricula positively influence career exploration and professional maturity, with no significant differences between the two. The MBKM curriculum's emphasis on real-world experience and career preparation was highlighted as a key factor in fostering career readiness. The study concludes that both curricula effectively support career development, but the MBKM curriculum offers a more practical, hands-on approach to preparing students for the workforce.